TECHNOLOGY AND THE PROVISION OF LONG-TERM CARE SERVICES AND SUPPORTS (LTSS) FOR OLDER ADULTS - Czaja, S.J. (Innov Aging, 2017)
The aging of the population, especially the increase in the “oldest old,” presents both opportunities and challenges. Although many older adults enjoy relatively good health, many have one or more chronic conditions or diseases and need help with disease management activities or activities important to independent living. There are a variety of technology applications such as sensing or monitoring technologies, telemedicine applications, or mobile device applications that can be used to enhance mobility and quality of life of people who have limitations and foster the ability of those with chronic conditions to remain at home. Technology can also provide a role in providing support to family caregivers. This paper will discuss the potential role that technology can play in the provision of LTSS for older adults and their families. Challenges and barriers that currently limit the full potential of technology to be realized for these populations will also be discussed.